Evaluation of properties of hybrid laminated composites with different fiber layers based on Coir/Al2O3 reinforced composites for structural application - Hasanuddin, Iskandar; Mawardi, Indra; Nurdin, N.; Putra Jaya, Ramadhansyah (Elsevier B.V., 2023)
Hybrid composites produced using natural and synthetic fibers are sustainable alternative materials for different structural applications. Therefore, this study aimed to incorporate coir fiber, E-glass, synthetic fabric, and rubber sheet into epoxy matrix by adding alumina filler to the coir composite. The hand layup method was used to manufacture a hybrid laminates composite of coir/E-glass/synthetic fabric/rubber sheet with different stacking sequences. The tensile, flexural, impact, hardness properties, water absorption, and thickness swelling of the products were evaluated. Scanning electron microscopy was used to study the morphology of the fractured surfaces. The results showed that the hybridization fiber and filler can enhance the tensile properties of the products up to 280% as well as improve the water absorption performance and thickness swelling to 78%. The flexural properties decreased after the incorporation of the fiber layer to the coir/alumina composite. An increase was also observed in the flexural and impact properties after the synthetic fabric was replaced with a rubber sheet. This study revealed that the incorporation of fibers layers into a coir composite led to higher hardness resistance. Furthermore, SEM image and macroscopic fractography showed fiber breakage on the matrix, a brittle fracture of composites, and delamination failure between the rubber sheet and matrix during the bending test. Based on the results, coir/E-glass/synthetic fabric/rubber sheet hybrid composites with different layering sequences were appropriate for various structures applications.